Assessment of the behavior of vertical ties in RC structures under progressive collapse. Issue 2 (22nd April 2019) - Droogné, Didier; Botte, Wouter; Caspeele, Robby
Abstract: Despite the recent amount of theoretical and technological developments, structural robustness is still an issue of controversy being underlined by several progressive collapses in the past. Current design codes point out different strategies, among which strategies to limit progressive structural damage by applying prescriptive design and detailing rules. For example, for consequence class 2 structures, EN1991‐1‐7 defines a risk class CC2b for which also vertical ties are required. However, the background of the design values of vertical ties in current codes is not clear and their adequacy should be validated. Moreover, effects such as membrane action and Vierendeel action are important to consider when assessing structural robustness and are difficult to incorporate when applying only traditional design methodologies. To this extent, a set of numerical simulations have been executed in this contribution in order to verify and investigate the progressive collapse behavior of RC frames including the redistribution of internal forces and the response of the vertical ties in columns.